2012
DOI: 10.5402/2012/637204
|View full text |Cite|
|
Sign up to set email alerts
|

Bedtime Single-Dose Prednisolone in Clinically Stable Rheumatoid Arthritis Patients

Abstract: Introduction. Sign and symptoms of rheumatoid arthritis have circadian rhythms and are more prominent in the morning. Timing of glucocorticoid administration may be important with respect to the natural secretion of endogenous glucocorticoids. Herein, we intended to test the hypothesis that bedtime administration of prednisolone could be more efficient in controlling signs and symptoms in patients with RA. Material and Methods. Sixty patients with stable disease were treated with single dose prednisolone at 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…Additionally, the impact of circadian rhythm on metabolite levels was strongly emphasizing the importance of time of the day-specific sampling and comparisons. Providing circadian rhythm-based glucocorticoid administration already helps to improve therapy and reduce side effects especially in long-term treatment 73 74 . A denser time series might allow detection of additional fine regulations.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the impact of circadian rhythm on metabolite levels was strongly emphasizing the importance of time of the day-specific sampling and comparisons. Providing circadian rhythm-based glucocorticoid administration already helps to improve therapy and reduce side effects especially in long-term treatment 73 74 . A denser time series might allow detection of additional fine regulations.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies had suggested a greater effect of bedtime or night doses (2:00 a.m.) in comparison with morning doses of conventional prednisone on morning stiffness [ 34 , 41 - 43 ]. However, a regimen that requires regular waking of the patient at 2:00 a.m. was considered impractical for the therapeutic routine.…”
Section: Does Modified-release Prednisone Aggravate Adrenal Suppressimentioning
confidence: 99%
“…Hence, administering GCs with long intervals (IV pulsed and/or oral alternate doses), short-term use (two to three weeks), and recruiting short half-life GCs (e.g., prednisone), and proper timing according to our study and years of experience. [ 14 15 ]…”
Section: The Issue Of Safe Immunomodulationmentioning
confidence: 99%